Second-order symmetric duality in multiobjective variational problems - Sachdev, Geeta; Verma, Khushboo; Gulati, T.R. (Yugoslav Journal of Operations Research, 2019)
In this work, we introduce a pair of multiobjective second-order symmetric dual variational problems. Weak, strong, and converse duality theorems for this pair are established under the assumption of η-bonvexity/η-pseudobonvexity. At the end, the static case of our problems has also been discussed.